Animação “Caliban Seed”: dos sonhos ao audiovisual - Rosa, Murillo Rodrigues [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The following work of completion (TCC) consists in the development of a 2D animation about the themes of images of unconsciousness, taking into account several dreams registered by the author. Combining the Concept Art, Illustration and Sound Design – specially the music – and influences of dreams in the arts, the objective becomes transmitting the sensation of an oneiric experience in a ludic manner that prevails in pop culture: through the Music Video.

O trabalho de conclusão de curso (TCC) a seguir consiste no desenvolvimento de uma animação 2D sobre a temática de imagens do inconsciente, levando em conta diversos sonhos registrados pelo autor. Unindo o Concept Art, Ilustrações e Sound Design - especialmente a música – e influências dos sonhos nas artes, o objetivo se torna transmitir a sensação de uma experiência onírica de maneira lúdica prevalente na cultura pop: através do Videoclipe.
Caliban seed animation: from dreams to audiovisual
Keywords: Concept art; Sound design; Dreams; Animation; Music video; Sonhos; Animação; Videoclipe